The Influence Of Happy Hour Promo And Store Atmosphere On Purchasing Decisions Through Consumer Satisfaction At Coffee Shop Declasse PJKA Kota Blitar - Mutiara, Hanif; Nabilah, Ghina (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This research aims to examine the influence of Happy Hour promo and store atmosphere on purchasing decisions through consumer satisfaction at Declasse PJKA Kota Blitar. The background of this study is the increasing competition among cafés in offering attractive promotions and creating a comfortable atmosphere to enhance customer experience and loyalty. This study uses a quantitative research approach with a survey method. Data were collected through questionnaires distributed to customers of Declasse PJKA, and the sample was determined using purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS software. The results show that Happy Hour promo has a positive and significant effect on consumer satisfaction, and store atmosphere also has a positive and significant influence on consumer satisfaction and purchasing decisions. Moreover, consumer satisfaction mediates the relationship between Happy Hour promo, store atmosphere, and purchasing decisions. These findings indicate that attractive promotional strategies and a pleasant store environment can enhance consumer satisfaction, which ultimately increases purchasing decisions. This research contributes to marketing management by emphasizing the importance of experiential and promotional factors in shaping consumer behavior in café businesses